Film-facilitated formation of ferrocenecarboxylic acid-embedded metal-organic framework nanoparticles for sonodynamic osteosarcoma treatment - Deng, Xiangyu (2023)
Sonodynamic therapy (SDT) has stronger penetrating ability compared with phototherapy due to the replacement of excitant from near-infrared light to ultrasound. The effective combination of low-intensity ultrasound and sonosensitizers allows SDT to penetrate deep tissue for the treatment of deep solid tumors. In this research, hybrid metal-organic framework (MOF) nanoparticles (FcCOOH-ZnTCPP, FcCOOH: ferrocenecarboxylic acid, TCPP: tetra(4-carboxyphenyl)porphyrin) are synthesized by a simple film technology, demonstrating outstanding acoustic response characteristics. FcCOOH is directly embedded in the nanoparticles during the formation process of FcCOOH-ZnTCPP, where FcCOOH catalyzes excess hydrogen peroxide in the tumor microenvironment to oxygen for increasing the SDT effect. Hybrid MOF nanoparticles with good biocompatibility and internalization ability to tumor cells present enhanced therapeutic effect to osteosarcoma on account of synergistic contributions of ZnTCPP and FcCOOH. This FcCOOH-ZnTCPP system may pave a new way for precise and efficient tumor inhibition.